Connectome analysis of male world‐class gymnasts using probabilistic multishell, multitissue constrained spherical deconvolution tracking. Issue 10 (10th July 2021) - Tomita, Hiroyuki; Kamagata, Koji; Andica, Christina; Uchida, Wataru; Fukuo, Makoto; Waki, Hidefumi; Sugano, Hidenori; Tange, Yuichi; Mitsuhashi, Takumi; Lukies, Matthew; Hagiwara, Akifumi; Fujita, Shohei; et al.
Abstract: In athletes, long‐term intensive training has been shown to increase unparalleled athletic ability and might induce brain plasticity. We evaluated the structural connectome of world‐class gymnasts (WCGs), as mapped by diffusion‐weighted magnetic resonance imaging probabilistic tractography and a multishell, multitissue constrained spherical deconvolution method to increase the precision of tractography at the tissue interfaces. The connectome was mapped in 10 Japanese male WCGs and in 10 age‐matched male controls. Network‐based statistic identified subnetworks with increased connectivity density in WCGs, involving the sensorimotor, default mode, attentional, visual, and limbic areas. It also revealed a significant association between the structural connectivity of some brain structures with functions closely related to the gymnastic skills and the D‐score, which is used as an index of the gymnasts' specific physical abilities for each apparatus. Furthermore, graph theory analysis demonstrated the characteristics of brain anatomical topology in the WCGs. They displayed significantly increased global connectivity strength with decreased characteristic path length at the global level and higher nodal strength and degree in the sensorimotor, default mode, attention, and limbic/subcortical areas at the local level as compared with controls. Together, these findings extend the current understanding of neural mechanisms that distinguish WCGs from controls and suggest brain anatomical network plasticity in WCGs resulting from long‐term intensive training. Future studies should assess the contribution of genetic or early‐life environmental factors in the brain network organization of WCGs. Furthermore, the indices of brain topology (i.e., connection density and graph theory indices) could become markers for the objective evaluation of gymnastic performance. Abstract : Using the MSMT‐CSD‐based connectome, we identified increased structural connectivity in Japanese male world‐class gymnasts (WCGs), involving sensorimotor, default mode, attentional, visual, and limbic subnetworks correlated with D‐scores of floor, parallel bars, horizontal bar, and years of training. Our findings indicated brain anatomical network plasticity in WCGs resulting from long‐term intensive training.